Knee functions and a return to sports activity in competitive athletes following anterior cruciate ligament reconstruction - Nakayama, Y.; Shirai, Y.; Narita, T.; Mori, A.; Kobayashi, K. (Journal of Nippon Medical School, 2000)
We investigated knee functions and a return to sports in 50 competitive athlete patients treated with arthroscopic anterior cruciate ligament reconstruction using double-looped STG augmented by woven polyester at a 1-year follow-up. There were 25 males and 25 females with a mean age of 24.3 years (range: 19-39 years). The majority of preinjury sports were basketball, volleyball and soccer. Athletic rehabilitation including agility training and sports-specific training was started at 12 weeks. Fourty patients (80%) was rated as normal or nearly normal on the assessment of International Knee Documentation Commitee postoperatively. Fourty-eight patients (96%) obtained full range of motion, and the mean quadriceps muscle strength of the injured side was 91.3%of that of the uninjured side. As for a return to sports, 46 patients (92%) were able to do fully competitive sports at a mean of 8.1 postoperative months. These results suggest that arthroscopic reconstruction using augmented double-looped STG allows early athletic rehabilitation, and lead satisfactory outcome as well as a reliable and early return to preinjury level of sport activity for the majority of the competitive athlete patients.